2022
DOI: 10.3390/brainsci12050656
|View full text |Cite
|
Sign up to set email alerts
|

The Applicability of Acceptance and Commitment Therapy for Obsessive-Compulsive Disorder: A Systematic Review and Meta-Analysis

Abstract: Background: Acceptance and commitment therapy (ACT), a third-generation cognitive behavioral therapy (CBT), has proved its efficacy amidst various mental disorders. A growing body of studies has shown that ACT can improve obsessive-compulsive disorder (OCD) severity in recent years. To assess the effect of ACT on OCD, we carried out a systematic review and meta-analysis to provide a basis for therapists to use different psychological dimensions of ACT for OCD. Methods: PubMed, the Cochrane Library, EMBASE, EBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The concept of psychological flexibility refers to the ability to connect with the present moment with conscious awareness, to stay in touch, to change one's behavior in line with needs and values, and to persevere in this behavior (Hayes et al, 1999). In a recent systematic evaluation and meta-analysis study, it was reported that patients diagnosed with OCD, in particular, learned to change their rapport with these symptoms instead of wrestling with intrusive obsessions and compulsions after ACT intervention, and thus recovery was associated with this mediator (Soondrum et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The concept of psychological flexibility refers to the ability to connect with the present moment with conscious awareness, to stay in touch, to change one's behavior in line with needs and values, and to persevere in this behavior (Hayes et al, 1999). In a recent systematic evaluation and meta-analysis study, it was reported that patients diagnosed with OCD, in particular, learned to change their rapport with these symptoms instead of wrestling with intrusive obsessions and compulsions after ACT intervention, and thus recovery was associated with this mediator (Soondrum et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies over the past two decades support ACT’s effectiveness in the treatment of various mental health difficulties; especially anxiety and related disorders (e.g., A-Tjak et al, 2015; Arch et al, 2012; Ferreira et al, 2022; Forman et al, 2007; Gloster et al, 2020; Karekla, 2005; Roemer et al, 2008; Soondrum et al, 2022). Moreover, many studies have shown that integration of ACT into exposure treatment for disorders, including agoraphobia, OCD and posttraumatic stress disorder has been both effective and acceptable, especially for more complex cases (e.g., Cullinan & Gaynor, 2015; Ramirez et al, 2021; Twohig et al, 2018).…”
Section: Exposure Therapy: Gold Standard or Room For Improvement?mentioning
confidence: 99%
“…ACT can help OCD patients embrace their experiences and strive toward meaningful areas of life, despite the presence of obsessions, anxiety, and compulsions. Although a recent meta-analysis, including a small number of studies, reports the applicability of ACT for OCD [ 47 ], it needs to be tested with more extensive RCTs in larger samples.…”
Section: Advances In Treatment For Ocd In Adultsmentioning
confidence: 99%